Effect of Different Media on the Bactericidal Activity of Colistin and on the Synergistic Combination With Azidothymidine Against mcr-1-Positive Colistin-Resistant Escherichia coli - Loose, Maria; Naber, Kurt G.; Coates, Anthony; Wagenlehner, Florian M. E.; Hu, Yanmin (Frontiers in Microbiology, 2020)
^Antimicrobial susceptibility testing (AST) performed according to defined guidelines is important to identify resistance and to predict the clinical success or failure of specific antibiotic therapy. However, these guidelines do not cover all physiological conditions that can have a tremendous impact on in-vivo resistance. In this study, we tested the susceptibility of thirteen mcr-1-positive Escherichia coli strains against colistin, one of the last resort antibiotics for treating multi-drug resistant pathogens, in media recommended for ASTs as well as - physiologically more relevant - in human serum and artificial urine. Minimal inhibitory concentration (MIC) values in heat-inactivated human serum were similar to those in cation-adjusted Mueller-Hinton broth (CAMHB), but reduced in native serum for almost all strains that could grow in this media. In artificial urine (AU) MIC values for mcr-1 positive E. coli were increased significantly up to 16-fold compared to that in CAMBH, which did not apply to the colistin-susceptible E. coli strains tested. Although different growth media could affect the MIC of colistin alone, their impact on the synergistic effect of the combination with the antiviral drug azidothymidine was minimal. The higher divalent cation concentration combined with acidic pH values is most likely responsible for the increased MIC values of the mcr-1 harbouring E. coli strains tested against colistin in AU compared to that in CAMHB. Antimicrobial susceptibility screening procedures for colistin using CAMHB only could lead to an underestimation of resistance under different physiological conditions. Therefore, not only pharmacokinetic but also pharmacodynamic studies in urine are as important as in serum or plasma.